Metasurface-based Circularly Polarized Dual-Port MIMO Antenna for C-band Uplink Applications - Supreeyatitikul, Nathapat; Boonpoonga, Akkarat; Phongcharoenpanich, Chuwong (My University, 2022)
The rectangular-shaped metasurface (MTS)- based circularly polarized (CP) dual-port MIMO antenna was proposed. The proposed rectangular-shaped MTS-based CP dual-port MIMO antenna included two substrate layers (upper and lower). The periodic 4×4 rectangular-shaped MTS elements on the upper layer functioned as CP polarizers. Also, the lower substrate layer comprised the microstrip probe feed and ground plane which generated a linearly polarized (LP) wave. The proposed rectangular-shaped MTS-based CP dual-port MIMO antenna at 5.3 GHz achieved impedance bandwidth (IBW) of 30.9% (4.86 - 6.5 GHz) and axial ratio (ARBW) of 14% (5.16 - 5.9 GHz). The maximum gain was 7.3 dBi at 5.1 GHz. The ECC was lower than 0.002, and DG was greater than 9.98 dB between entire frequency ranges. The direction of the radiation was right-hand circular polarization (RHCP). The dimension of proposed rectangular-shaped MTS-based CP dual-port MIMO antenna was 1.342λ0 × 0.652λ0 × 0.0372λ0.
Keywords: Circularly polarized antenna; Metasurface; MIMO antenna; Polarizer; Right-hand circular polarization